Hands-free sample preparation platform for nucleic acid analysis. - MARTIN, CARA; KEEGAN, HELEN; O'LEARY, JOHN (My University, 2009)
A Lab-On-Chip system with an instrument is presented which is capable of performing total sample preparation and automated extraction of nucleic acid from human cell samples fixed in a methanol based solution. The target application is extraction of mRNA from cervical liquid based cytology specimens for detection of transformed HPV-infections. The device accepts 3 ml of sample and performs the extraction in a disposable polymer chip of credit card size. All necessary reagents for cell lysis, washing, and elution are stored on-chip and the extraction is performed in two filter stages; one for cell pre-concentration and the other for nucleic acid capture. Tests performed using cancer cell lines and cervical liquid based cytology specimens confirm the extraction of HPV-mRNA by the system.
PUBLISHED
Keywords: Medical laboratory technology; Lab-On-Chip; mRNA